Nanotechnology as a Novel Approach in Combating Microbes Providing an Alternative to Antibiotics - Bismillah Mubeen; Aunza Nayab Ansar; Rabia Rasool; Inam Ullah; Syed Sarim Imam; Sultan Alshehri; Mohammed M. Ghoneim; Sami I. Alzarea; Muhammad Shahid Nadeem; Imran Kazmi (MDPI AG, 2021)
The emergence of infectious diseases promises to be one of the leading mortality factors in the healthcare sector. Although several drugs are available on the market, newly found microorganisms carrying multidrug resistance (MDR) against which existing drugs cannot function effectively, giving rise to escalated antibiotic dosage therapies and the need to develop novel drugs, which require time, money, and manpower. Thus, the exploitation of antimicrobials has led to the production of MDR bacteria, and their prevalence and growth are a major concern. Novel approaches to prevent antimicrobial drug resistance are in practice. Nanotechnology-based innovation provides physicians and patients the opportunity to overcome the crisis of drug resistance. Nanoparticles have promising potential in the healthcare sector. Recently, nanoparticles have been designed to address pathogenic microorganisms. A multitude of processes that can vary with various traits, including size, morphology, electrical charge, and surface coatings, allow researchers to develop novel composite antimicrobial substances for use in different applications performing antimicrobial activities. The antimicrobial activity of inorganic and carbon-based nanoparticles can be applied to various research, medical, and industrial uses in the future and offer a solution to the crisis of antimicrobial resistance to traditional approaches. Metal-based nanoparticles have also been extensively studied for many biomedical applications. In addition to reduced size and selectivity for bacteria, metal-based nanoparticles have proven effective against pathogens listed as a priority, according to the World Health Organization (WHO). Moreover, antimicrobial studies of nanoparticles were carried out not only in vitro but in vivo as well in order to investigate their efficacy. In addition, nanomaterials provide numerous opportunities for infection prevention, diagnosis, treatment, and biofilm control. This study emphasizes the antimicrobial effects of nanoparticles and contrasts nanoparticles' with antibiotics' role in the fight against pathogenic microorganisms. Future prospects revolve around developing new strategies and products to prevent, control, and treat microbial infections in humans and other animals, including viral infections seen in the current pandemic scenarios.